THE DIAGNOSIS OF PSORIATIC ARTHRITIS - P.S. Helliwell (PAGEPress Publications, 2011)
For over 30 years investigators have used the simple but non-validated classification criteria suggested by Moll and Wright. Several authors have suggested modifications but most remain invalid or require HLA analysis. Now, a world wide initiative has developed new criteria (the CASPAR criteria) which include both clinical, laboratory and radiological features. These will require further study before they are fully adopted for future studies but their improved performance should result in less variation between study cohorts. Key words: Psoriatic arthritis, classification criteria, diagnosis